2012
DOI: 10.1016/j.jacc.2011.11.030
|View full text |Cite
|
Sign up to set email alerts
|

Electroanatomic Remodeling of the Left Stellate Ganglion After Myocardial Infarction

Abstract: Objectives The purpose of this study was to evaluate the changes of left stellate ganglionic nerve activity (SGNA) and left thoracic vagal nerve activity (VNA) after acute myocardial infarction (MI). Background Whether MI results in remodeling of extracardiac nerve activity remains unclear. Methods We implanted radiotransmitters to record the SGNA, VNA, and electrocardiogram in 9 ambulatory dogs. After baseline monitoring, MI was created by 1-h balloon occlusion of the coronary arteries. The dogs were then… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
110
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(118 citation statements)
references
References 18 publications
8
110
0
Order By: Relevance
“…Heterogeneous postinfarct sprouting of sympathetic nerves has been reported in humans and animals (12,26,29,30). Neurotrophins released at the infarct site are trafficked to stellate ganglia (29) and presumably the intrinsic cardiac network (ICN), where they induce neuronal remodeling (2,4,9), increase stellate ganglion nerve activity (9), and cause sprouting of sympathetic nerves in the heart. The porcine model of patchy myocardial scars showed nerve sprouting and increased nerve density at scar-border zone regions consistent with previous findings (13,21).…”
Section: Discussionmentioning
confidence: 99%
“…Heterogeneous postinfarct sprouting of sympathetic nerves has been reported in humans and animals (12,26,29,30). Neurotrophins released at the infarct site are trafficked to stellate ganglia (29) and presumably the intrinsic cardiac network (ICN), where they induce neuronal remodeling (2,4,9), increase stellate ganglion nerve activity (9), and cause sprouting of sympathetic nerves in the heart. The porcine model of patchy myocardial scars showed nerve sprouting and increased nerve density at scar-border zone regions consistent with previous findings (13,21).…”
Section: Discussionmentioning
confidence: 99%
“…We used heart rate and systolic blood pressure as surrogates of generalized sympathetic activity. Nevertheless, these are indirect hemodynamic indexes that reflect global sympathetic activation, and they may not always correlate with alterations in myocardial sympathetic nerve activity, which have been measured using in vivo recordings in dogs (12,31). The latter studies demonstrate that increased sympathetic nerve activity precedes the development of ventricular arrhythmias and displays a diurnal variation resulting in myocardial sympathovagal imbalance that is maximal in the morning (8 AM to 12 PM) and correlates with the time frame during which spontaneous VT/VF developed in our swine model.…”
Section: Discussionmentioning
confidence: 99%
“…Follow-up studies demonstrated that myocardial infarction causes the upregulation of proteins that contributed to nerve growth (nerve growth factor, growth-associated protein 43, and synaptophysin) in both the infarcted site 72 and the more upstream bilateral stellate ganglia. 73 Interestingly, sympathetic nerve sprouting itself can lead to an increased incidence of VF without concomitant cardiac ischemia. It was found that rabbits given a high-cholesterol diet developed myocardial hypertrophy and cardiac sympathetic hyperinnervation without coronary artery disease along with an increased vulnerability to VF.…”
Section: Ventricular Tachyarrhythmiasmentioning
confidence: 99%
“…Although increased stellate ganglion nerve activity contributes to VF and SCD in myocardial infarction, acute myocardial infarction itself can cause an increase in nerve activity and nerve density of the LSG-electroanatomic remodeling. 73 This generates a vicious cycle that can lead to more ischemia, VF, and SCD.…”
Section: Ventricular Tachyarrhythmiasmentioning
confidence: 99%